Determination of the Infectious Agent of Translucent Post-Larva Disease (TPD) in Penaeus vannamei - Ying Zou; Guosi Xie; Tianchang Jia; Tingting Xu; Chong Wang; Xiaoyuan Wan; Yingxia Li; Kun Luo; Xiaodong Bian; Xiuhua Wang; Jie Kong; Qingli Zhang (Pathogens, 2020)
A new emerging disease called “translucent post-larvae disease” (TPD) or “glass post-larvae disease” (GPD) of Penaeus vannamei, characterized by pale or colorless hepatopancreas and digestive tract, has become an urgent threat to the shrimp farming industry. Following this clue that treatment of an antibacterial agent could alleviate the disease, systematic investigation of the potential infectious agent of TPD was conducted using bacterial identification and artificial challenge tests to fulfill Koch’s postulates. A dominant bacterial isolate, Vp-JS20200428004-2, from the moribund individuals was isolated and identified as Vibrio parahaemolyticus based on multi-locus sequence analysis. However, Vp-JS20200428004-2 differed from the V. parahaemolyticus that caused typical acute hepatopancreatic necrosis disease. Immersion challenge tests revealed that Vp-JS20200428004-2 could cause 100% mortality within 40 h at a dose of 1.83 × 106 CFU/mL, and experimental infected shrimp showed similar clinical signs of TPD. The Vp-JS20200428004-2 could be re-isolated and identified from the experimental infected individuals. Moreover, histopathological analysis of diseased samples indicated that Vp-JS20200428004-2 caused severe necrosis and sloughing of epithelial cells of the hepatopancreas and midgut in shrimp individuals both naturally and experimentally infected. Our present results indicated that Vp-JS20200428004-2 is a highly virulent infectious agent associated with the TPD and deserves further attention.